Prarancangan Pabrik Cumene dari Propilen dan Benzena dengan Proses Q-Max kapasitas 110.000 Ton/Tahun - Jumarmi, Jumarmi, Eni Budiyati, S.T, M.Eng (2017)
Cumen is a chemical substance that has a lot of benefits in the chemical industry. One of the benefits as a raw material for phenol and acetone. Cumen is produced by using alkylation reaction of benzene and propylene in the gases phase takes place in a fixed bed multitube reactor with the help of beta zeolite catalyst. Alkylation reaction works at the temperature of 350oC and pressure of 25 atm. Formation reactions of cumen works by non isothermal and non-adiabatic and runs irreversible. Cumen plant requires raw materials of propylene is 4.913,6903 kg / hour, while benzene is 2.7363,5164 kg / hour. Cumen which generated is as much as 13.843,7780 kg / hour. Utility is a support unit for process that provides steam 12336.2281 kg / hour, cooling water makeup 17696.005 kg / hour, the air pressure of 50 kg / hr, 325.4975 kW of electricity and fuel as much as 212.8531 m3. Cumene plant is planned will be established in 2020 in the industry area at Cilegon, Banten. Fixed capital invesment (FCI) of this plant is Rp 422.240.231.601, working capital is 150.459/683.272. From the economic analysis it is shown that the percent return on investment (ROI) before the taxes is 54,48% and after the taxes is 40,86%. Pay out time (POT) before taxes is 1,55 years and after taxes is 1,97 years. Break event point (BEP) is 43,85% while shut down point (SDP) is 28,37%. From the result of the economics analysis the cumene plant with Q-Max process is feasible to set up.